Philosophy Teaching in Secondary Schools of Lithuania - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2000)
The article presents an empirical investigation of the philosophy teaching in Lithuanian secondary school nowadays. To know the situation of philosophy teaching is important for specialists, involved in creating of the concept. A few aspects were taken into the account: content, textbooks, teachers’ qualification, students’ motivation, interest and assessment, teachers of philosophy from secondary schools were questioned. The results show the difference between teaching philosophy in ordinary school and gymnasium. The dominant program structure is history of philosophy and other one - parts of philosophical system. The most popular textbook- M. Furst, J. Trinks "Philosophy". Teacher's qualification is not very high. The student's assessment is good in spite of different interests and motivations.
Keywords: Secondary school; gymnasium; subject of philosophy; philosophy teaching.